Brood sex ratio and nestling physiological condition as indicators of the influence of weather conditions on breeding black storks Ciconia nigra. (September 2019) - Kamiński, Maciej; Bańbura, Jerzy; Janic, Bartosz; Kaldma, Katrin; Konovalov, Annika; Marszał, Lidia; Minias, Piotr; Väli, Ülo; Zieliński, Piotr
Highlights: The paper examines the influence of weather on Black Stork nestlings sex ratio. Temperatures in the pre-breeding period negatively correlate with nestling male ratio. Rainfalls in the hatching period negatively correlate with nestling male ratio. Delayed broods have lower nestling male ratio. Male nestlings have poorer body condition. Abstract: In species with sexual dimorphism, raising female or male offspring may be associated with different costs and benefits, resulting in a skewed nestling sex ratio. We examined the influence of: weather conditions, hatching date and brood size on nestling sex ratio in the black stork Ciconia nigra . We used molecular methods to determine the sex of 284 nestlings. Samples were collected during a 12-years study in central Poland. The overall nestling sex ratio was skewed towards females (61%), which are smaller, and presumably easier to raise than males. Delayed hatching date significantly increased the proportion of female nestlings. Warmer temperatures in the pre-breeding season were correlated with lower proportions of males. This is probably mediated by the influence of weather on water levels in black stork foraging sites. The second most important weather trait was total rainfall in May, the month in which the majority of nestlings hatch. Total May rainfall was negatively correlated with the percentage of male offspring. We used blood haemoglobin concentration as an indicator of body condition in a subsample of 122 nestlings. The males from the study population had lower blood haemoglobin concentrations, indicating their poorer body condition and supporting the hypothesis that they are the more vulnerable sex. We also observed that blood haemoglobin concentration of nestlings is lower in late broods. Deteriorating body condition of late offspring can explain the observed increase in female nestling proportions in delayed broods.